Revisiting the trade and unemployment nexus: Empirical evidence from the Nigerian economy - Stephen T. Onifade; Ahmet Ay; Simplice Asongu; Festus Victor Bekun (African Governance and Development Institute (AGDI), 2019)
The recent exacerbation of unemployment crisis in Nigeria stands to be a serious threat to both socio-economic stability and progress of the country just as the report from the nation's bureau of statistics shows that at least over 8.5 million people had no gainful employment at all as at the last quarter of the year 2017. It is on the above premise, that the present study explores the link between trade and unemployment for the case of Nigeria with the intention of exploring how the unemployment crisis has been impacted within the dynamics of the country's trade performance. The empirical evidence shows that the nation's terms of trade were insignificant to unemployment rate while trade openness and domestic investment, on the other hand, have significant opposing impacts on unemployment in Nigeria over the period of the study. Further breakdowns from the empirical analysis also revealed that the Philips curves proposition is valid within the Nigerian economic context while the evidences for the validity of Okun's law only exist in the short-run scenario. Based on the empirical results, we recommend that concerted effort should be geared toward stimulating domestic investment by providing adequate financial and infrastructural facilities that will promote ease of doing business while utmost precautions are taken to ensure that unemployment crisis is not exacerbated when combating inflation in the economy in the wake of dynamic trade relations.
Keywords: E23; F21; F30; O16; O55; 330; Nigeria; Unemployment; Trade; Phillips Curves; Okun's law